Insolvency costs and incomplete information in commercial banks: Implications for financial reform in Eastern Europe - Claudia M. Buch (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
The development of financial markets in the emerging market economies of Eastern Europe is considered one of the crucial elements of the overall reform process. Under central planning, banks used to be passive recipients of orders from the planners; they did not engage in any credit screening activity. At the same time, financial intermediaries have the potential to assume an important role in the transformation process from plan to market. They could gather information on enterprises, sort out profitable investment opportunities, finance these projects, and monitor the appropriate utilization of the invested funds. However, an efficient process of financial intermediation is currently being hampered by at least two factors. First, the balance sheets of many banks are loaded with non-performing loans. The presence of these loans exposes banks to a high risk of insolvency. Secondly, there is evidence that credit markets are segmented due to informational asymmetries. In particular, new private enterprises seem to have difficulties in obtaining external finance. The purpose of this paper is to present a framework which suits to analyze the effects of these obstacles to an efficient process of financial intermediation. The major conclusions can be summarized as follows. If banks have positive costs of insolvency, they will reduce lending and raise interest rates as the share of non-performing loans on their balance sheets increases. However, in the presence of incomplete information on borrowers, banks may choose to ration credit rather than to adjust interest rates upwards. More specifically, asymmetric information can give a rationale for private enterprises being credit rationed. Because of the lack of collateral in private firms, which might serve as a sorting device, investment into information by the banks should be given priority. The paper starts by giving an overview over some stylized facts of Eastern European financial markets (part two). In the third part, the financial liberalization literature is briefly reviewed. After that, a microeconomic framework of the behavior of banks is presented. At the end of the paper, the main findings are summarized.
Keywords: 330; Bilanzstrukturmanagement; Kreditrationierung; Kapitalmarktliberalisierung; Bankrisiko; Unvollkommene Information; Osteuropa